The sugar cane alcohol´s income during the nascent Republic of Colombia, 1819-1828: debates around the tobacconist and liberalization - Pita Pico, Roger (2021)
On the occasion of the commemoration of the Bicentennial of the Independence of the Hispano-American nations and, within the framework of social history and economic history, the objective of this article focuses on analyzing the sugar cane alcohol’s income during the second republican phase in the period between 1819 and 1828 in Colombia, observing in detail the advances and vicissitudes, as well as the changes and permanence in the management of this branch of the economy that oscillated between the state monopoly and liberalization during this phase in which the foundations of a new nation were being laid.